Teacher perspectives on the development of business English programmes in the Thai tertiary context : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Applied Linguistics at Massey University, Palmerston North, New Zealand - Amatayakul, Panithi (Massey University, 2019)
Business English has emerged as an important aspect of English for Specific Purposes in Thailand and is currently provided as an undergraduate programme in about one third of all universities. However, to date we know relatively little about how the Business English programme has been developed in the Thai tertiary context. The current study aimed to explore the development of Business English programmes in the past, present, and future, through the perspectives of Thai tertiary teachers. Firstly, the development of Business English programmes in two university contexts was explored, based on retrospective interviews with five experienced teachers. In addition, a survey which included open-ended scenarios was completed by Business English teachers (N=84) from throughout Thailand (North, Northeast, Central, and South), regarding their contemporary perspectives on Business English in the Thai tertiary context and future prospects for the field. Finally, in-depth interviews were conducted with 13 Business English teachers, focusing particularly on their contemporary perspectives on Business English and the trajectory of Business English as a tertiary subject. Overall, the findings revealed that the contemporary tertiary Business English programmes emerged from both bottom-up and top-down initiatives, and were shaped by local factors such as ongoing changes to curriculum and teaching practices. The development of the programmes was also influenced by a combination of external factors, including the government policy, English as a Lingua Franca in the Asia region and global pressures. The teachers who participated in this study thought that the future changes would be in line with these contemporary changes. It was also evident that future programmes might continue to face both internal and external challenges. The thesis concluded by reflecting on future challenges which needed to be addressed and the resulting implications for research, professional development, and practice.
Keywords: English language; Business English; Study and teaching (Higher); Thailand; College teachers; English teachers; Attitudes; 470401 Applied linguistics and educational linguistics